2019
DOI: 10.37358/rc.19.9.7530
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Obesity and Periodontal Disease after Minimally Invasive Sleeve Gastrostomy

Abstract: Obesity is a complex and multifactorial disease. Its relationship with periodontal disease and other chronic diseases is well documented but the underlying mechanism is under investigation. It is quite difficult to say whether obesity predisposes an individual to periodontal disease or periodontal disease affects lipid metabolism, or both. The purpose of the study consists in evaluating the periodontal clinical parameters in obese patients diagnosed with chronic periodontitis, before and after surgical treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Hypothesizing that inflammation, represented through increased values of IL-6 and CRP, correlated with leptin in patients following acute myocardial infarction, could be due to the involvement of leptin in the signaling cascade following myocardial ischemia, the study of Karthick et al showed a relationship between serum leptin and IL-6 levels, demonstrating leptins' involvement in inflammatory cytokine upregulation during heart ischemia [39,40].…”
Section: Correlations Between Obesity and Pro-inflammatory Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothesizing that inflammation, represented through increased values of IL-6 and CRP, correlated with leptin in patients following acute myocardial infarction, could be due to the involvement of leptin in the signaling cascade following myocardial ischemia, the study of Karthick et al showed a relationship between serum leptin and IL-6 levels, demonstrating leptins' involvement in inflammatory cytokine upregulation during heart ischemia [39,40].…”
Section: Correlations Between Obesity and Pro-inflammatory Statusmentioning
confidence: 99%
“…Phillips et al reported a positive benefit of weight loss through surgical procedures after a period of weight stabilization. Because of the cell diversity that produces the same cytokines, body weight loss as a result of bariatric surgery improves one specific set of cytokine-producing cells' metabolic phenotype, causing a reduction in a specific cytokine from that tissue, but this may drive production in another cell type in the short term [40,41].…”
Section: Correlations Between Obesity and Pro-inflammatory Statusmentioning
confidence: 99%